Effect of substituting non-polar chains with polar chains on the structural dynamics of small organic molecule and polymer semiconductors. Issue 12 (24th March 2021) - Guilbert, Anne A. Y.; Parr, Zachary S.; Kreouzis, Theo; Woods, Duncan J.; Sprick, Reiner Sebastian; Abrahams, Isaac; Nielsen, Christian B.; Zbiri, Mohamed
Abstract : Probing chain-dependent structure and dynamics on the microscopic scale using neutron spectroscopy provides insights into structural disorder of organic semiconductors. Abstract : The processability and optoelectronic properties of organic semiconductors can be tuned and manipulated via chemical design. The substitution of the popular alkyl side chains by oligoethers has recently been successful for applications such as bioelectronic sensors and photocatalytic hydrogen evolution. Beyond the differences in polarity, the carbon–oxygen bond in oligoethers is likely to render the system softer and more prone to dynamical disorder that can be detrimental to charge transport for example. In this context, we use neutron spectroscopy as a master method of probe, in addition to characterisation techniques such as X-ray diffraction, differential scanning calorimetry and polarized optical microscopy to study the effect of the substitution of n -hexyl (Hex) chains by triethylene glycol (TEG) chains on the structural dynamics of two organic semiconducting materials: a phenylene–bithiophene–phenylene (PTTP) small molecule and a fluorene- co -dibenzothiophene (FS) polymer. Counterintuitively, inelastic neutron scattering (INS) reveals a general softening of the modes of PTTP and FS materials with Hex chains, pointing towards an increased dynamical disorder in the Hex-based systems. However, temperature-dependent X-ray and neutron diffraction as well as INS and differential scanning calorimetry evidence an extra reversible transition close to room temperature for PTTP with TEG chains. The observed extra structural transition, which is not accompanied by a change in birefringence, can also be observed by quasi-elastic neutron scattering (QENS). A fastening of the TEG chains dynamics is observed in the case of PTTP and not FS. We therefore assign this transition to the melt of the TEG chains. Overall the TEG chains are promoting dynamical order at room temperature, but if crystallising, may introduce an extra reversible structural transition above room temperature leading to thermal instabilities. Ultimately, a deeper understanding of chain polarity and structural dynamics can help guide new materials design and navigate the intricate balance between electronic charge transport and aqueous swelling that is being sought for a number of emerging organic electronic and bioelectronic applications.